Recent Advances in Imaging and Pathological Techniques for Diagnosing Tubercular Lymphadenitis(EPTB) In Children and Adolescents Up To 14 Years - Vijay Kulshrestha (Asian Journal of Medical Radiological Research, 2019)
Background: Lymphadenitis is the most common manifestation of extra pulmonary tuberculosis (EPTB), there is still a diagnostic challenge due to its similarity with other pathological conditions. Recent imaging techniques are very helpful in approaching the diagnosis of nodal tuberculosis. Further confirmation of diagnosis is done by staining for acid fast bacilli, fine needle aspiration cytology, and excisional biopsy & by histo-pathological analysis. High Resolution sonography contributesin diagnosis of various types of lymph nodes, and endobronchial ultrasound mainly useful for mediastinal and hilar lymph nodes.Recent advances like C.T. scan, MRI and PET-CT demonstrates site,pattern ,and extent of disease .These imaging modalities can better differentiates between benign from malignant causes .The Ultrasound  /C.T guided FNAC/ Biopsy further plays an important role in confirmation of diagnosis with staining /culture /histo-pathological analysis.   It is also important to differentiate tuberculosis from non-tubercular mycobacterial lymphadenitis. HIV co-infection also plays important role in further increase the cases of lymphadenitis.